2022
DOI: 10.3390/w14010119
|View full text |Cite
|
Sign up to set email alerts
|

Aspergillus niger Culture Filtrate (ACF) Mediated Biocontrol of Enteric Pathogens in Wastewater

Abstract: Robust control of pathogens in sewage facilitates safe reuse of wastewater rich in valuable nutrients for potential valorization through biological means. Aspergillus niger is widely reported in bioremediation of wastewater but studies on control of enteric pathogens in sewage are very sparse. So, this study aimed at exploring the antibacterial and nematicidal activity of A. niger culture filtrate (ACF). Antibacterial activity of ACF on enteric pathogens (Klebsiella pneumoniae, Pseudomonas aeruginosa, Vibrio c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…In one of the few studies showing that A. niger has antimicrobial properties, Subhash et al (2022) evaluated the antibacterial activity of A. niger culture filtrate (ACF) against enteric pathogens Escherichia coli, Klebsiella pneumoniae, K. variicola, Pseudomonas aeruginosa, Salmonella enterica, Shigella dysenteriae, Staphylococcus aureus and Vibrio cholerae and demonstrated that ACF inhibited the growth of these pathogens (Subhash et al 2022). Similarly, in our study, A. niger culture filtrate was found to have antimicrobial activity against S. aureus and MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…In one of the few studies showing that A. niger has antimicrobial properties, Subhash et al (2022) evaluated the antibacterial activity of A. niger culture filtrate (ACF) against enteric pathogens Escherichia coli, Klebsiella pneumoniae, K. variicola, Pseudomonas aeruginosa, Salmonella enterica, Shigella dysenteriae, Staphylococcus aureus and Vibrio cholerae and demonstrated that ACF inhibited the growth of these pathogens (Subhash et al 2022). Similarly, in our study, A. niger culture filtrate was found to have antimicrobial activity against S. aureus and MRSA.…”
Section: Discussionmentioning
confidence: 99%
“…The susceptibility of the strains (RS and T1) to antibiotics was evaluated by the antibiotic sensitivity test by conventional Kirby-Bauer disc diffusion assay [ 32 ] with 10 different antibiotics, amoxicillin, (10mcg) chloramphenicol (30mcg), penicillin G (2 U), gentamicin (10 mcg), cefoxitin (30mcg), streptomycin (10 mcg), ampicillin (10mcg), amikacin (30mcg), erythromycin (15mcg), tetracycline (30mcg) (HiMedia). Overnight cultures of strains with OD (600) of 1 were swabbed uniformly across MRS agar plates; the antibiotic discs were placed and incubated for 24 h at 37°C.…”
Section: Methodsmentioning
confidence: 99%
“…In the L4 stage, the worms were exposed to the following treatments (a) C. elegans + S. enterica (b) C. elegans + S. enterica + BLIS from RS (c) C. elegans + S. enterica + antibiotic (ciprofloxacin 20 μg/mL) (positive control) and (d) C. elegans + M9 buffer (control). The survival percentage of the worms treated with BLIS was compared with L4 worms in M9 broth, and the survival curves were plotted and compared ( 32 ).…”
Section: Methodsmentioning
confidence: 99%
“…The isolates of Bacillus spp. and Pseudomonas putida were isolated from soil, while Escherichia coli sequence type 155 (Salim et al 2019) and Klebsiella variicola (Subhash et al 2022) were isolated from sewage at the Sanitation Biotechnology Lab, School of Biotechnology, Amrita Vishwa Vidyapeetham, Kerala, India. All the bacterial strains were maintained in Luria-Bertani (LB) at 37 °C.…”
Section: Bacterial Culturesmentioning
confidence: 99%